2014
DOI: 10.4236/cellbio.2014.33010
|View full text |Cite
|
Sign up to set email alerts
|

Ameliorative Action of Mn-Salen Derivatives on CCl<sub>4</sub>-Induced Destructive Effects and Lipofuscin-Like Pigment Formation in Rats’ Liver and Brain: Post-Treatment of Young Rats with EUKs

Abstract: How to cite this paper: Meftah, S., Yazdanparast, R. and Molaei, M. (2014)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…Thus, the authors reported that EUK-8 and EUK-134 reduced the sera aminotransferases, the extent of lipid peroxidation, low density lipoprotein contents, cholesterol, and protein carbonylation. The same research group published another study about the protective effects of EUK-8, EUK-15, EUK-115, EUK-122, EUK-132, and EUK-134 against CCl 4 -induced damages in rats [ 150 ]. The manganosalen complexes ameliorated the effects of CCl 4 by decreasing the levels of ROS, lipid and protein oxidations, and lipofuscin-like pigments formation on the liver and brain.…”
Section: Therapeutic Effects Of Manganosalen Complexes In In Vivo mentioning
confidence: 99%
“…Thus, the authors reported that EUK-8 and EUK-134 reduced the sera aminotransferases, the extent of lipid peroxidation, low density lipoprotein contents, cholesterol, and protein carbonylation. The same research group published another study about the protective effects of EUK-8, EUK-15, EUK-115, EUK-122, EUK-132, and EUK-134 against CCl 4 -induced damages in rats [ 150 ]. The manganosalen complexes ameliorated the effects of CCl 4 by decreasing the levels of ROS, lipid and protein oxidations, and lipofuscin-like pigments formation on the liver and brain.…”
Section: Therapeutic Effects Of Manganosalen Complexes In In Vivo mentioning
confidence: 99%
“…Thus, the authors reported that EUK-8 and EUK-134 reduced the sera aminotransferases, the extent of lipid peroxidation, low density lipoprotein contents, cholesterol, and protein carbonylation. The same research group published other study about the protective effects of EUK-8, EUK-15, EUK-115, EUK-122, EUK-132 and EUK-134 against CCl4-induced damages in rats [154]. The manganosalen complexes ameliorated the effects of CCl4 by decreasing the levels of ROS, lipid and protein oxidations and lipofuscin-like pigments formation on liver and brain.…”
Section: Adrenal and Liver Diseasesmentioning
confidence: 88%
“…Carbon tetrachloride (CCl 4 ) is a widely used as an environmental toxicant model and well known to generate ROS, induce lipid peroxidation, damage to different organs, including the liver, kidneys, heart, brain and testis [3]. The mechanism by which CCl 4 induce its toxicity mainly due to the bio-activation into trichloromethyl peroxy radical ( • OOCCl 3 ) and trichloromethyl radical ( • CCl 3 ) by the cytochrome P450 [4].…”
Section: Introductionmentioning
confidence: 99%